Wood or charcoal? - Keita, Jean-Djiqui (Technical Centre for Agricultural and Rural Cooperation, 1988)
Jean-Djiqui Keita Jean-Djiqui Keita was born in Mali and educated in France. He was Chief of the Soils Conservation Division, Forestry Directorate and then Director of Forestry, Fisheries and Wildlife in Mali. Since 1978 he has been the FAO Senior...